HUBUNGAN PANJANG LENGAN DAN KEKUATAN TUNGKAI DENGAN KEMAMPUAN RENANG - Indah, Eka Purnama; Hardiyono, Bayu (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2019)
This study aims to determine the relationship between arm length and leg strength and swimming ability. This research is a descriptive correlational type of research. The study population was all students of the Sport Education Study Program FKIP Bina Darma University Palembang with a total sample of 80 people selected by proportional random sampling. The data analysis technique used is a simple and multiple correlation analysis technique. Based on the results of data analysis, this study concluded that: There was a significant relationship between arm length and swimming ability (ro = 0.585> rt = 0.220); There was a significant relationship between leg strength and swimming ability (ro = 0.673> rt = 0.220); There is a significant relationship between arm length and leg strength and swimming ability (Ro = 0.681> Rt = 0.220).